Aging, Social Security Design, and Capital Accumulation - Dedry, Antoine (World Bank, Washington, DC, 2015)
This paper analyzes the impact of aging on capital accumulation and welfare in a country with a sizable unfunded social security system. Using a two-period overlapping generation model with endogenous retirement decisions, the paper shows that the type of aging and the type of unfunded social security system are important in understanding this impact. The analysis compares two types of demographic changes, declining fertility and increasing longevity; three types of pensions, defined contributions, defined benefits, and defined annuities; as well as mandatory and optimal retirement systems to investigate the differences in implications of aging.